2021
DOI: 10.1029/2020ea001628
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of FY‐2G Atmospheric Motion Vector Data and Assimilating Impacts on Typhoon Forecasts

Abstract: Atmospheric motion vectors (AMVs) have produced positive impacts on global weather forecasts, but few studies have evaluated the impacts of AMV data from the Fengyun (FY) geostationary satellite series, especially from FY‐2G and FY‐4, on typhoon forecasts in a regional model. In this study, the qualities of FY‐2G and Himawari‐8 AMV data are comparatively evaluated with several preprocesses (e.g., height assignment, quality control, channel merging, thinning, and observation error assignment) employed, and a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Liu et al (2012) used Weather Research and Forecasting Model Data Assimilation (WRFDA) system to assimilate the AMVs data retrieved from FY-2C infrared and water vapor channels, and showed that the reasonable selection of AMVs data added to the numerical weather prediction (NWP) model was beneficial to supply the meso-scale information not included in the initial fields, as well as improving the prediction ability of the model. In order to assess the qualities and assimilating impacts of the AMVs retrieved from the first generation of the Chinese Fengyun geostationary satellite, the AMVs data of FY-2G and Himawari-8 were evaluated by Liang et al (2021) in typhoon forecasts with the conclusions that both AMVs data have showed comparably positive forecasting impacts even though the AMVs quality of Himawari-8 were overall better.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2012) used Weather Research and Forecasting Model Data Assimilation (WRFDA) system to assimilate the AMVs data retrieved from FY-2C infrared and water vapor channels, and showed that the reasonable selection of AMVs data added to the numerical weather prediction (NWP) model was beneficial to supply the meso-scale information not included in the initial fields, as well as improving the prediction ability of the model. In order to assess the qualities and assimilating impacts of the AMVs retrieved from the first generation of the Chinese Fengyun geostationary satellite, the AMVs data of FY-2G and Himawari-8 were evaluated by Liang et al (2021) in typhoon forecasts with the conclusions that both AMVs data have showed comparably positive forecasting impacts even though the AMVs quality of Himawari-8 were overall better.…”
Section: Introductionmentioning
confidence: 99%